Prognostic factors for salvage endoscopic resection for esophageal squamous cell carcinoma after chemoradiotherapy or radiotherapy alone - Kondo, Shinya; Tajika, Masahiro; Tanaka, Tsutomu; Kodaira, Takeshi; Mizuno, Nobumasa; Hara, Kazuo; Hijioka, Susumu; Imaoka, Hiroshi; Goto, Hidemi; Yamao, Kenji; Niwa, Yasumasa (Endoscopy International Open, 2016)
Background and study aims: Endoscopic resection is one treatment option for residual or locally recurrent esophageal cancer after definitive chemoradiotherapy or radiotherapy alone. However, little is known about the clinical benefit of salvage endoscopic resection for these lesions. Therefore, the effectiveness and prognostic factors of salvage endoscopic resection were investigated.Patients and methods: A total of 37 patients with esophageal squamous cell carcinoma (SCC) who underwent salvage endoscopic resection after definitive chemoradiotherapy or radiotherapy alone were reviewed. The method of salvage endoscopic resection was endoscopic mucosal resection using a cap (EMR-C), strip biopsy, or endoscopic submucosal dissection. The effectiveness and prognostic factors of salvage endoscopic resection were retrospectively analyzed.Results: A total of 37 patients with 49 lesions underwent salvage endoscopic resection. Baseline clinical stages were I in 23 patients, II in 3 patients, III in 9 patients, and IV in 2 patients. The number of locoregional recurrences and residual lesions were 35 and 14, respectively. The curative en bloc resection rate was 53.1 % (26/49). The total incidence of complications was 18.9 % (7/37); all were successfully managed conservatively. The 3-year and 5-year overall survival rates were 72.9 % and 53.3 %, respectively, with a median follow-up period of 54 months. Baseline clinical T1 – 2 and N0 were significant factors for good prognosis in terms of overall survival on univariate analysis.Conclusions: Salvage endoscopic resection, especially EMR-C, is a safe and feasible procedure to control residual or recurrent superficial esophageal SCC after definitive chemoradiotherapy or radiotherapy alone. The present results showed that baseline clinical T1 – 2 and N0 before chemoradiotherapy or radiotherapy were significant prognostic factors.